(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
After the BPSh operation, all patients showed a significant decrease in the level of hemoglobin, ferritin and serum iron, starting from the 3rd month after the operation and progressively continuing throughout the entire observation period of the patients (7 years).